Jihad in the Book Of Al-Mishbah: Overview Schleiermacher’s Romantic Hermeneutic - Atin Suhartini (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This article will elaborate on the understanding of the importance of jihad from the understanding of Al-Mishbah from the perspective of hermeneutics as an art method of understanding. Quraish Shihab as an observer who is isolated from the debate, many people only see from his experience that he is often seen as close to Shia culture. To avoid the wrong impression among readers and journalists in understanding the text of the jihad verse, this article uses the Schleiermacher hermeneutics method as one of the objective hermeneutics, namely understanding is in the author of the text. Schleiermacher’s hermeneutics will not only look at the text but also look at the psychological side or life of Quraish Shihab especially when he is writing the commentary on al-Mishbah. The results of this study indicate that through the grammatical interpretation of the meaning of jihad in the interpretation of Al-Mishbah it is understood that, first, the meaning of jihad in the interpretation of Al-Mishbah is an outer and inner struggle against religious enemies. Second, jihad by taking up arms is the last resort in jihad against religious enemies. Furthermore, through his psychological interpretation, Quraish Shihab is a person who has superior capacity and conditions that support him in writing the interpretation of Al-Mishbah